Students' Experiences Towards Debate Competition As Part Of Their Critical Thinking Development - Nabila Azhar; Rizka Zahra Amalia; Silvi Sultonah; Tria Moulina, (Journal of Applied Linguistics (ALTICS), 2024)
This qualitative study aimed to explore the experiences of three college students who participated in a recent debate competition and how it contributed to their development of critical thinking skills. The study used semi-structured interviews to gather data, which was then analysed and interpreted using thematic analysis. The results showed that the debate competition provided a platform for the students to engage in critical thinking and develop skills such as analysis, reasoning, and evaluation. The students also reported an increase in confidence and a greater appreciation for diverse perspectives. Overall, the study highlights the potential benefits of debate competitions in promoting the development of critical thinking skills among college students. Keywords: English English Debate Competition, Critical Thinking Development, Student Experience, Learning outcomes, Communication skills, Problem-solving, Decision-making.